Making globalization work - Stiglitz, Joseph E. (Allen Lane, 2006)
"Four years ago, Joseph E. Stiglitz outlined the problems our rapidly integrating world was facing in Globalization and Its Discontents." "Now, in Making Globalization Work, Stiglitz brings the story up to the present, examining how change has occurred occurred even more rapidly over the past four years, proposing solutions, and looking to the future. He puts forward radical new ways of dealing with the crippling indebtedness of developing countries, recommends a new system of global reserves to overcome international financial instability, and provides new proposals for addressing the current impasse in dealing with global warming - the most important threat to the world's environment. He argues for the reform of global institutions - the United Nations, the International Monetary Fund, and the World Bank - as well as for international trade agreements and intellectual property laws to make these institutions truly capable of responding to the problems of our age. Throughout, Stiglitz makes a compelling case that treating developing countries more fairly is not only morally right but is ultimately to the advantage of the developed world too."--BOOK JACKET.